Effect of different training programs on the velocity of overarm throwing: a brief review - van den Tillaar, R. (The Journal of Strength and Conditioning Research, 2004)
Throwing velocity in overarm throwing is of major importance in sports like baseball, team handball, javelin, and water polo. The purpose of this literature review was to give an overview of the effect of different training programs on the throwing velocity in overarm throwing, provide a theoretical framework that explains findings, and give some practical applications based on these findings. The training studies were divided into 4 categories: (a) specific resistance training with an overload of velocity, (b) specific resistance training with an overload of force, (c) specific resistance training with a combination of overload of force and velocity, and (d) general resistance training according to the overload of force. Each category is presented and discussed.